Defendant's Ignorance of State Administrative Court Decision Contempt Of Court - pondayar, yustus (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
In a state of law, the existence of the State Administrative Court is the most important part of the repressive efforts to protect the community to obtain justice and legal certainty. It is impossible for the Defendant to cancel the decision of the State Administrative Court for several reasons: first, there is no execution institution in the State Administrative Court, second, there are no legal sanctions, and third, ignoring the decision of the State Administrative Court creates legal uncertainty for the Plaintiff. In addition, the Defendant's ignoring the decision constitutes a ignoring of the general principles of good governance. The Defendant's attitude includes committing unlawful acts (unfair government actions) or arbitrary (desire or shift of power). The actions of state administrative bodies/officials who do not comply with and carry out the decision of the State Administrative Court judge can be categorized as acts that are contrary to the law.